TIPE KEPRIBADIAN PEREMPUAN TOKOH MAHARANI DALAM NOVEL AIR MATA MAHARANI KARYA VENNIA LESTARI - Erlina Zahar; Serlina Lubis (Universitas Batanghari, 2022)
The purpose of this study is to describe the types of oersonality of the female character Maharani in the novel Air Mata Maharani by Vennia Lestari. The female personality type consists of four types, namely sanguinis, choleric, melancholy, and plegmatic. This research is included in the type of qualitative descriptive research. Qualitative descriptive research is research intended to investigate circumstances, conditions or other things, the results of which are presented in the form of research reports in the form of data. The data of this study are findings in the form of quotations in the novel Air Mata Maharani by Vennia Lestari. The results of this study contained the female personality type of the Maharani character in the Novel Air Mata Maharani by Vennia Lestari. Based on the results of this study, it can be concluded that the type of female personality of the Maharani character in the novel Tears of the Maharani was found to be four types. The most dominant type is the sanguinis female personality type which is twenty-three, while the slightly choleric female type is nine quotes.